A COMPARATIVE ANALYSIS OF THE DERMATOGLYPHICS THROUGH PHYSICAL TESTS TO VERIFY THE INNATE PHYSICAL CAPACITIES (Fiep Bulletin - online, 2015)
The objective of this study is to compare the physical capacities, resistance, speed, coordination and agility (GRECO and BENDA, 1998), to the genetic potential (SKINNER, 2002).  In this work, it was used as sample, welded of the masculine sex, of the CIA School of 2º Military Body Firemen Battalion of  Minas Gerais State, N=26 with age 23,5 + 2,85, where all had passed for the same criteria of training and evaluation.  The protocols had been considered by Santos and Filho (2004), in the attainment of the genetic profile, used it Dermatoglyphics and in the evaluation of the physical capacities;  aerobic resistance (VO2máx.)_  test of Cooper;  coordination _ Burpee;  agility _ Shuttle Run:  already anaerobic resistance _ test of 300m and speed race _ test of 40m, by Macedo (1999).  The sample was divided in respective digital formulas, where each group possess specific physical characteristics as Abramova et al. (cited by Santos and Filho, 2004).  In the comparison of the samples the test of Kruskal-Wallis with p=0,05. was used having significant difference does not enter the results of the carried through tests.  The research evidenced the influence of phenotype, helped out with Skinner (2002), where bigger genetic influence in the structural components is verified, that in the functionaries, these, they suffer great influence from the training and the environment.  In accordance with the average values and shunting line-standard (10LVO2máx.), the applied tests had tended to confirm the project of Nikitchuk et al. (cited for Filho, 2003).  The Dermatoglyphs is suggested then as tool to be used to optimize a physical evaluation, however new research, relating it with the physical capacities must be carried through.  Not being possible esteem with precision the answers of the individual to the training, the findings of this study they agree with citations of Skinner (2002), when affirming that successful athletes are those that, had initiated its trainings with superior levels of the necessary characteristics and/or had presented superior adaptations after-exercise, essential to the success.
Keywords: Dermatoglifia; phenotype; genotype